(+)-CSA Catalyzed Multicomponent Synthesis of 1-[(1,3-Thiazol-2-ylamino)methyl]-2-naphthols and Their Ring-Closure Reaction under Ultrasonic Irradiation - Pelit, Emel; Turgut, Zuhal (HINDAWI LTD, 2016)
New 1-[(1,3-thiazol-2-ylamino)methyl]-2-naphthols were obtained by condensation of 2-aminothiazole, aromatic aldehydes, and 2-naphthol in the presence of (+)-camphor-10-sulfonic acid ((+)-CSA) as an effective catalyst under ultrasound-promoted solvent-free conditions. The 1-[(1,3-thiazol-2-ylamino) methyl]-2-naphthol derivatives were converted in ring-closure reaction with formaldehyde to the corresponding naphthoxazine derivatives.
Keywords: ONE-POT SYNTHESIS; THIAMINE HYDROCHLORIDE VB1; MANNICH REACTION; STEREOSELECTIVE SYNTHESIS; CONFORMATIONAL-ANALYSIS; EASY ACCESS; DERIVATIVES; FACILE; EFFICIENT; GREEN; Chemistry